2018
DOI: 10.3389/fncel.2018.00204
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor Receptor 1 in the Anterior Cingulate Cortex Mediates Maternal Absence-Induced Attenuation of Transport Response in Mouse Pups

Abstract: A human infant initially shows non-selective sociality, and gradually develops selective attachment toward its caregiver, manifested as “separation anxiety.” It was unclear whether such sophistication of attachment system occurs in non-human mammals. To seek a mouse model of separation anxiety, we utilized a primitive attachment behavior, the Transport Response, in that both human and mouse newborns immediately stop crying and stay immobile to cooperate with maternal carrying. We examined the mouse Transport R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…We have previously demonstrated that human infants and mouse pups can be calmed immediately by parental carrying and that it reduces their cry, spontaneous movements, and their heart rate, partly mediated by the parasympathetic activation [ 10 , 26 , 42 , 43 ]. This evolutionarily conserved set of physiological and behavioral responses to carrying is termed the "Transport Response" and is widely observed across mammalian species, regarded as infant cooperative responses to parental carrying [ 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that human infants and mouse pups can be calmed immediately by parental carrying and that it reduces their cry, spontaneous movements, and their heart rate, partly mediated by the parasympathetic activation [ 10 , 26 , 42 , 43 ]. This evolutionarily conserved set of physiological and behavioral responses to carrying is termed the "Transport Response" and is widely observed across mammalian species, regarded as infant cooperative responses to parental carrying [ 4 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The upper graph indicates infant body weight growth. Transport Response occurs during the transition from oral carrying by mother to walking on their own ( Esposito et al., 2013 ; Yoshida et al, 2013 , 2018 ). …”
Section: Developmental Changes In Sensorimotor Reflexes To Being Carriedmentioning
confidence: 99%
“…After the end of the stress hyporesponsive period at postnatal day 14, the expression of Transport Response becomes increasingly social context dependent. Transport Response was suppressed when the mother was not present in the home cage or when the pup was alone in the novel environment ( Figure 5 B) ( Yoshida et al., 2018 ). The activation of the anterior cingulate cortex that is due to corticotropin-releasing hormone from the paraventricular nucleus is thought to underlie this social context-dependent suppression of Transport Response ( Yoshida et al., 2018 ).…”
Section: Developmental Changes In Sensorimotor Reflexes To Being Carriedmentioning
confidence: 99%
See 1 more Smart Citation
“…Early-life trauma has been associated with alterations in ACC connectivity, volume and thickness, and it has been hypothesized that maltreatment leads to impaired ACC role in the threat detection and response system, thus increasing vulnerability to psychopathologies (McCrory et al, 2017;McCrory & Viding, 2015;Teicher et al, 2016). ACC sensitivity to ELS has been confirmed in animal studies (Banqueri et al, 2021;Yoshida et al, 2018), which showed that ACC bears long-term morphometric and functional alterations following early adversity (Gos et al, 2008;Helmeke et al, 2001Helmeke et al, , 2008Salberg et al, 2021;Spinelli et al, 2009). The molecular mechanisms linking early stress with ACC dysfunctions and psychopathological outcomes are still under investigation.…”
Section: Introductionmentioning
confidence: 96%